Pengaruh Pembiayaan Mudharabah Dan Pembiayaan Bermasalah Terhadap Profitabilitas Dengan Dana Pihak Ketiga Sebagai Variabel Moderating Pada Bank Umum Syariah Di Indonesia - muhammad sofian; irfan irfan; Widia Astuty (Jurnal Riset AKuntansi dan Bisnis, 2020)
This research aims to find out how much influence Mudharabah Financing and Problematic Financing have on Profitability with Third Party Funds as moderating variables at Sharia Commercial Banks in Indonesia. This type of research with a statistical descriptive approach. The research methodology used is a method of documentation and study of literature. The data source comes from secondary data, which comes from Sharia Banking Statistics published by the Financial Services Authority. The data used in this study is data on 14 Sharia Commercial Banks in Indonesia from January 2015 to December 2019. The analytical tools used in this study are multiple linear regressions. The results of this study show that Mudharabah Financing has no significant effect on profitability, but Problematic Financing negatively and significantly affects profitability, while Third Party Funds do not moderate the influence of Mudharabah Financing on Profitability and Third Party Funds also do not moderate the effect of Problematic Financing on profitability